2022
DOI: 10.3389/fped.2022.943529
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vitamin D supplementation in hospitalized COVID-19 pediatric patients: A randomized controlled trial

Abstract: BackgroundSome studies suggested that adequate levels of vitamin D (VD) decrease the risk of severe COVID-19. Information about the effectiveness of VD supplementation in children is scarce.ObjectiveTo assess the efficacy and safety of VD supplementation compared to the standard of care in hospitalized children with COVID-19.Patients and methodsAn open-label randomized controlled single-blind clinical trial was carried out. We included patients from 1 month to 17 years, with moderate COVID-19, who required hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 48 publications
(44 reference statements)
1
36
0
1
Order By: Relevance
“…As such, it is important to start vitamin D supplementation in children. This point is supported by a more recent randomized controlled trial done by Zurita-Cruz et al [ 49 ].…”
Section: Discussionmentioning
confidence: 56%
“…As such, it is important to start vitamin D supplementation in children. This point is supported by a more recent randomized controlled trial done by Zurita-Cruz et al [ 49 ].…”
Section: Discussionmentioning
confidence: 56%
“…These challenges and sources of bias in studying the link between VD concentrations and SARS-CoV-2 epidemiology can explain the widely discordant evidence between studies [ 28 , 29 ]. In fact, while the results from observational cross-sectional studies generally indicate that VD insufficiency is strongly associated with SARS-CoV-2 infection and severity [ 22 , 23 , 28 , 29 , 45 , 46 ], evidence from interventional RCTs on VD supplementation in COVID-19 are more discordant, both in terms of prophylactic [ 29 , 47 ] and therapeutic effectiveness [ 48 , 49 , 50 , 51 ]. In our cohort, the absence of extremely impactful differences in VD status between positive and negative patients and COVID-19 severity classes can also be due to the low frequency of extremely low VD levels among our patients, who in most cases already take VD supplementation (40.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that vitamin D supplementation led to only two COVID-19 patients requiring ventilation compared with nine patients in the control group. The vitamin D-supplemented group only had one mortality compared with six in the control group, while the patients supplemented with vitamin D also presented a lower hospital admittance period [ 125 ].…”
Section: Vitamin D Regulationmentioning
confidence: 99%